Unraveling gender dynamics in migration and remittances: an empirical analysis of Asian women's “exposure to migration” - Ullah, AKM Ahsan (2024)
The concept of “exposure to migration” helped us understand family dimensions, such as the role of members who remained behind, especially wives, changing gender roles, and changing exposure to remittances. However, most existing migration studies have not examined whether exposure to migration has anything to do with gender dynamics. This has often resulted in women or wives playing a subordinate role in contemporary discourse on gendered migration. Because they have very little to do with remittances compared to male family members, their role in the family is viewed critically by their male counterparts. This research is based on interviews with women from a selection of countries in Asia. Based on the analytical framework of “exposure to migration”, this study contends that the degree of exposure to migration for women depends on the country’s social and cultural milieu. In many cases, this exposure also leads to marital problems and family complications.